Perlindungan Hukum terhadap Anak Sebagai Korban Kekerasan yang Terjadi di Sekolah - Felda Rizki Azalia (Universitas Batanghari Jambi, 2020)
Acts of violence experienced by children, especially in schools are of concern to the Indonesian Child Protection Commission. This becomes the background that needs to be reviewed further about the legal protection received by children as victims of school violence, as we know that the school is a place to educate children to become educated human beings. The role of a teacher is as a parent in school, should provide appropriate education and learning, not to be a person against violence against students at school. The focus of the problem that will be discussed is first, what are the factors that cause high acts of violence against children in schools that occur in Indonesia at this time and second how the actions taken by KPAI and the Government in overcoming problems of violence against schools like what is happening in Indonesia today . This paper uses the research method used is normative legal research that uses the method of gathering legal material is a literature study or documentary study. The expected outcome of this research is to give an appeal to teachers, parents and students so that schools need to be involved in the supervision of their students and carry out some roles that schools can take to protect their children or students by resuming the teacher's function as a moral educator and devoted to God Almighty, provides motivation and enthusiasm, especially from parents at home to teach children to think positively about the violence that has happened to him.